Time continuous vs time discrete analysis of the take off technique in long jump - Jaitner, T. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Long jump trials of specialist long jumpers, decathlete and sports students were filmed two-dimensional with one high speed camera. Performance during Take-Off (TO) was analyzed based on time continuous data. All trials were compared for similarity and classified by cluster analysis (Schöllhorn, 1999). Additional cluster analyses considered time discrete variables only. For both data sets, no classification according to jumping performance was found. The results indicate that different TO strategies may result in comparable jumping performance. Consequences on the analysis and training of sports